Dissociated α-Band Modulations in the Dorsal and Ventral Visual Pathways in Visuospatial Attention and Perception. (31st October 2012) - Capilla, Almudena; Schoffelen, Jan-Mathijs; Paterson, Gavin; Thut, Gregor; Gross, Joachim
Abstract : Modulations of occipito-parietal α-band (8–14 Hz) power that are opposite in direction (α-enhancement vs. α-suppression) and origin of generation (ipsilateral vs. contralateral to the locus of attention) are a robust correlate of anticipatory visuospatial attention. Yet, the neural generators of these α-band modulations, their interdependence across homotopic areas, and their respective contribution to subsequent perception remain unclear. To shed light on these questions, we employed magnetoencephalography, while human volunteers performed a spatially cued detection task. Replicating previous findings, we found α-power enhancement ipsilateral to the attended hemifield and contralateral α-suppression over occipito-parietal sensors. Source localization (beamforming) analysis showed that α-enhancement and suppression were generated in 2 distinct brain regions, located in the dorsal and ventral visual streams, respectively. Moreover, α-enhancement and suppression showed different dynamics and contribution to perception. In contrast to the initial and transient dorsal α-enhancement, α-suppression in ventro-lateral occipital cortex was sustained and influenced subsequent target detection. This anticipatory biasing of ventro-lateral extrastriate α-activity probably reflects increased receptivity in the brain region specialized in processing upcoming target features. Our results add to current models on the role of α-oscillations in attention orienting by showing that α-enhancement and suppression can be dissociated in time, space, and perceptual relevance.